Exploring metastatic breast cancer treatment changes during COVID-19 pandemic. (19th May 2021) - Fedele, Palma; Ferro, Antonella; Sanna, Valeria; La Verde, Nicla; Paris, Ida; Chiari, Rita
Abstract : The emergency caused by COVID-19 pandemic has imposed a sudden reorganization of the healthcare structures and has created consequences in cancer patients management. General clinical recommendations for cancer patients were released, even if limited clinical cancer-specific data were available. A number of critical issues have come out during COVID-19 pandemic in the management of patients with metastatic breast cancer (MBC). To explore the changes in the treatment of patients with MBC during COVID-19 pandemic, we promoted a survey to the oncologists operating in the Italian breast units. The results of this survey show that Italian oncologists have tried to ensure continuity of care for patients with MBC. De-escalation of cancer treatments, especially monotherapy administration, and greater use of oral anticancer drugs are the main changes that emerge from this survey. Some subgroups of patients, especially the elderly and endocrine-responsive patients, have been undertreated during the COVID-19 pandemic.